Perceived and physiological strains of societal participation in people with multiple sclerosis: a real-time assessment study - Arianne S. Gravesteijn; Maaike Ouwerkerk; Isaline C.J.M. Eijssen; Heleen Beckerman; Vincent de Groot (Journal of Rehabilitation Medicine, 2024)
Objective: To examine the relationship between perceived and physiological strains of real-time societal participation in people with multiple sclerosis.